Filter aid selection allows modulating the vanadium concentration in beverages. (1st December 2019) - May, Bianca; Dreifke, Tim; Patz, Claus-Dieter; Schütz, Christian L.; Schweiggert, Ralf; Dietrich, Helmut
Highlights: Vanadium (V) concentrations in certain beverages were analyzed. Differences between clear and cloudy juices indicated an influence of processing. Substantial V amounts were detected in certain filter aids. Pilot scale filtration trials proved the transfer of V from filter aid to juice. Choice of the filter aid has a significant impact on the V in the final product. Abstract: This study reports a clear-cut relationship of the technological use of specific filter aids with highly variable vanadium levels in beer, wine, and fruit juices. First, the previously reported broad range of vanadium levels was confirmed in 68 commercial beverages by ICP-MS. Since cloudy apple juices exhibited significantly lower vanadium amounts than clear apple juices, filter aids used for clarification were analyzed and found to contain substantial and highly variable amounts of vanadium, particularly in all analyzed diatomite (38–368 mg vanadium per kg filter aid), but not in perlite products (<4 mg/kg). Subsequent pilot-scale precoat filtration experiments (170 L/batch) proved vanadium to be released from diatomite (Kieselguhr), increasing its levels from ca. 2.1–2.6 µg/kg unfiltered to 27–201 µg/kg filtered juice, depending on the use of diatomites high or low in vanadium. Thus, filter aid selection was shown to modulate the vanadium concentrations in clarified beverages.